1991
DOI: 10.1111/j.1438-8677.1991.tb01557.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake and allocation byCalluna vulgaris(L.) Hull andDeschampsia flexuosa(L.) Trin. exposed to15NH3

Abstract: SUMMARY The transition of Dutch heathlands dominated by Calluna vulgaris to grass heaths occurs rapidly and is primarily ascribed to nitrogenous air pollution. C. vulgaris and Deschampsia flexuosa were fumigated with 15NH3 and the adsorption of ammonia to the leaf surface as well as the uptake and translocation of ammonia nitrogen was determined after 4 and 9 weeks. There appeared to be little or no NH3‐nitrogen adsorbed to the leaf surface of either species. D. flexuosa took up more NH3 per unit shoot weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Fangmeier et al (1994), reviewed the effects of NH 3 on vegetation, including the effects of NH 3 on moorland vegetation. There have been a number of studies of NH 3 effects on the Dutch heathland vegetation, but these were glasshouse/laboratory experiments and not field scale studies Van der Eerden et al (1991) and Dueck et al (1991). We are not aware of any other studies with treatment application regimes that simulate the real world's exposure of vegetation to NH 3 .…”
Section: Resultsmentioning
confidence: 96%
“…Fangmeier et al (1994), reviewed the effects of NH 3 on vegetation, including the effects of NH 3 on moorland vegetation. There have been a number of studies of NH 3 effects on the Dutch heathland vegetation, but these were glasshouse/laboratory experiments and not field scale studies Van der Eerden et al (1991) and Dueck et al (1991). We are not aware of any other studies with treatment application regimes that simulate the real world's exposure of vegetation to NH 3 .…”
Section: Resultsmentioning
confidence: 96%
“…heathland and chalk grassland (Van Dam, 1990;Van der Eerden et al, 1991). The eflfects of eutrophication on chalk grassland, as reported by Van Dam (1990), illustrate the widespread threat to habitats other than those already tending to be acidic.…”
Section: Its Effect On Vegetation and Ecosystemsmentioning
confidence: 97%
“…Nitrogen enrichment of heathland on nutrient-poor sandy soils has led to a spread of grasses such as Molifiia caerulea, Deschampsia flexuosa, and Festuca ovina, which are able to outcompete the ericaceous species (Berendse & Aerts, 1984;Roelofs, 1986;Van Breeman & Van Dijk, 1988;Van der Eerden et al, 1991). Van der Eerden et al (1991) found that heathland species are relatively sensitive to atmospheric ammonia. In monoculture Calluna increased its shoot growth when fumigated or watered with ammonia, but when it was grown in competition with Deschampsia flexuosa, the latter species was able to outgrow it.…”
Section: Its Effect On Vegetation and Ecosystemsmentioning
confidence: 99%
“…Furthermore, Dueck et al. (1991) reported that NH 3 is mainly taken up through plant stomata instead of cuticles. As a consequence, N deposition in the form of gaseous NH 3 was found to have greater effects on moorland vegetation than wet-deposited (Leith et al.…”
Section: Discussionmentioning
confidence: 99%